DINAMIKA PARTAI POLITIK DALAM PEMILIHAN UMUM 2024 - Muklis, Marcelinus (Universitas Wijaya Kusuma Surabaya, 2025)
This study aims to analyze the dynamics of political parties in the 2024 general election, focusing on the strategies and adjustments made by political parties in response to the social and political changes occurring. In this context, the research explores how political parties adapt their approaches to attract increasingly diverse and critical voter support. The method employed in this research is a digital literature study, which involves the collection and analysis of data from various online sources, including articles, reports, and relevant policy documents. The analytical technique used is thematic analysis, which allows the researcher to identify patterns and themes that emerge from the collected data, as well as to understand the broader context of current political dynamics. The findings indicate that political parties that can quickly adapt to changes in political dynamics and voter preferences tend to be more successful in gaining support. Additionally, this research identifies the challenges faced by political parties in maintaining their relevance amid rapid changes. This study provides valuable insights for stakeholders in designing more effective strategies to address the challenges in the upcoming general election, emphasizing the importance of flexibility and innovation in campaign strategies.